2010
DOI: 10.1002/ijc.24836
|View full text |Cite
|
Sign up to set email alerts
|

The forkhead box M1 transcription factor as a candidate of target for anti‐cancer immunotherapy

Abstract: The present study attempted to identify a target antigen for immunotherapy for cholangiocarcinoma. Forkhead box M1 (FOXM1) was selected as a candidate antigen based on the data of previous cDNA microarray analysis of clinical samples of cholangiocarcinoma. The level of FOXM1 mRNA was more than 4 times higher in cancer cells in comparison to adjacent normal epithelial cells, in all of 24 samples of cholangiocarcinoma tissues. An immunohistochemical analysis also detected FOXM1 protein in the cancer cells but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…These data agree with another report that showed absence or minimal expression of FoxM1 in normal tissue from various organ sites as compared to their cancer counterparts. 42 Our data also showed that proliferative marker Ki67 was strongly associated with FoxM1 overexpression suggesting that FoxM1 deregulation may be driving the survival and proliferation of DLBCL cells.…”
Section: Discussionsupporting
confidence: 71%
“…These data agree with another report that showed absence or minimal expression of FoxM1 in normal tissue from various organ sites as compared to their cancer counterparts. 42 Our data also showed that proliferative marker Ki67 was strongly associated with FoxM1 overexpression suggesting that FoxM1 deregulation may be driving the survival and proliferation of DLBCL cells.…”
Section: Discussionsupporting
confidence: 71%
“…Fourthly, clinicopathologic studies suggest that FoxM1 expression correlated with poorly-differentiated HCC tumors with intrahepatic metastasis, which is a leading cause of post-surgical recurrence and low survival rate [20, 29]. Finally, silencing of FoxM1 expression could inhibit human hepatocellular carcinoma growth [30], and FoxM1 has been reported an underlying therapeutic target because it can be presented to cell surface by tumor cells [31]. Therefore, FoxM1 is considered as a novel therapeutic target for HCC drug therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, the frequency of peptide-specific CD4 þ T cells producing [24][25][26]. All mAbs were used at a final concentration of 5 mg/mL.…”
Section: Assessment Of T-cell Responses To Peptides and Proteinsmentioning
confidence: 99%